Polyploidy and introgression in invasive giant knotweed (Fallopia sachalinensis) during the colonization of remote volcanic islands. Issue 1 (December 2018) - Park, Chong-Wook; Bhandari, Gauri; Won, Hyosig; Park, Jin; Park, Daniel
Abstract Invasive giant knotweed (Fallopia sachalinensis ) is native to northeastern Asia. In Korea, F. sachalinensis is confined to two volcanic islands, Ullung and Dok islands, where it occurs as dodecaploids (2n = 132). We investigated the molecular variation in 104 accessions from 94 populations ofF. sachalinensis and its relatives throughout their native range to elucidate the origin of these island populations. AllF. sachalinensis plants on Ullung and Dok islands were uniquely dodecaploid, whereas other populations were tetraploid (2n  = 44). Among the 39 cpDNA haplotypes identified, the accessions from these islands shared two unique haplotypes, and were resolved as a well-supported monophyletic clade. However, this clade was sister to a clade comprisingF. japonica accessions from southwestern Japan and separated from the clade comprisingF. sachalinensis from other areas; this relationship is inconsistent with morphological evidence. The monophyly of theF. sachalinensis populations on Ullung and Dok islands suggests a single colonization event. The progenitor was likely from Japan, where it possibly capturedF. japonica var.japonica cpDNA via introgression. The Ullung Island populations subsequently differentiated through polyploidization and mutations post-introduction. Our results also indicate that giant knotweed in Europe and North America likely originated from northern Japan and/or Sakhalin Island.